Efficiency of social policy in equalizing disposable ncome and its changes in time – A cross-national comparison - Wysocki, Tomasz (Publishing House of the Wrocław University of Economics, 2009)
In his famous book Anarchy, State, and Utopia R. Nozick notices that although it is often assumed inequality of possibilities should be fought, there are few arguments for such a fight [Nozick 1974]. But in the light of a very strong argument formulated earlier by J. Rawls in the revolutionary A Theory of Justice the problem seems to be rather how to justify any deviation from full equality. Rawls says that no arbitrary distribution of life conditions should affect individuals’ life opportunities. Distribution of talents, disabilities, inherited goods or geographical conditions is arbitrary; therefore it is necessary to level their effects on human life [Rawls 1974]. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 463-474